Monte-carlo modeling for unstable particle ensembles with thermal fluctuations - Kharchenko, D.O. (Вопросы атомной науки и техники, 2009)
In this presentation we study binary alloy systems subjected to particle irradiation and
thermal noise influence. We discuss two competing mechanisms of the system evolution:
dynamics driven by irradiation and stochastic influences bringing the system toward thermal
equilibrium. Using a phase-field formalism and Monte-Carlo modeling we consider selforganization
processes in binary alloy systems with field/concentration dependent
mobility/diffusion coefficient. Generalization of the phase separation scenario and patterning
in such systems are presented. Досліджуються системи бінарних сплавів, підданих опроміненню часток і впливу
теплових шумів. Обговорюються два конкуруючих механізми еволюції системи: динаміка,
обумовлена опроміненням і стохастичні впливи, що переводять систему до теплової
рівноваги. З використанням формалізму теорії фазового поля і статистичного
моделювання розглядаються процеси самоорганізації у системах бінарних сплавів з
рухомістю, яка залежить від поля концентрації. Запропоноване узагальнення сценаріїв
фазового розшарування і структуроутворення у таких системах. Исследуются системы бинарных сплавов, подверженных облучению частиц и
воздействию тепловых шумов. Обсуждаются два конкурирующих механизма эволюции
системы: динамика, вызванная облучением, и стохастические воздействия, переводящие
систему к тепловому равновесию. С использованием формализма теории фазового поля и
статистического моделирования рассматриваются процессы самоорганизации в системах
бинарных сплавов с подвижностью, зависимой от поля концентрации. Предложено
обобщение сценария фазового расслоения и структурообразования в таких системах.